Cranial magnetic resonance imaging in chronic demyelinating polyneuropathy. - Hawke, S H (1990)
Twenty one patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and five patients with chronic demyelinating polyneuropathy associated with benign monoclonal paraproteinaemia none of whom had signs or symptoms of central nervous system disease, had cranial magnetic resonance imaging (MRI) on a 1.5 Tesla unit. Areas of increased white matter signal intensity were seen in one of 10 patients aged less than 50 years and in five of 16 patients aged more than 50 years. In only two of the patients (8%), neither of whom had paraproteinaemia, did the appearance strongly suggest demyelination. The only clinical variable that predicted MRI changes was age (p less than 0.01).